2021
DOI: 10.3390/pathogens10060739
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of hBD-2, hBD-3, hCAP18/LL37, and Proinflammatory Cytokine Secretion by Human Milk Oligosaccharides in an Organotypic Oral Mucosal Model

Abstract: Human milk oligosaccharides (HMOs), the third largest solid fraction in human milk, can modulate inflammation through Toll-like receptor signaling, but little is known about their immunomodulatory potential in the oral cavity. In this study, we determined whether the HMOs 2’-fucosyllactose (2’-FL) and 3-fucosyllactose (3-FL) regulate human-beta defensin (hBD)-2 and -3, cathelicidin (hCAP18/LL-37), and cytokine responses in human gingival cells using a three-dimensional oral mucosal culture model. The model was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Only two years after the discovery of the discussed molecule, it was shown that it is an important defense component in the oral cavity—hBD-2 is secreted by epithelial cells of the gingival mucosa, which is confirmed both by the expression of mRNA for hBD-2 in these cells and the presence of its product in saliva [ 18 ]. It has been shown that the increase of hBD-2 production in an oral mucosal culture model may be a result of an action of human milk oligosaccharides [ 19 ], which may be important in improving immunity in infants. Interestingly, studies involving children aged from 3 to 16 showed that the levels of both hBD-1 and hBD-2 in saliva increased with age, which concurs with the maturation of the immune system [ 20 ].…”
Section: Hbd-2 and Oral Cavity Epitheliummentioning
confidence: 99%
“…Only two years after the discovery of the discussed molecule, it was shown that it is an important defense component in the oral cavity—hBD-2 is secreted by epithelial cells of the gingival mucosa, which is confirmed both by the expression of mRNA for hBD-2 in these cells and the presence of its product in saliva [ 18 ]. It has been shown that the increase of hBD-2 production in an oral mucosal culture model may be a result of an action of human milk oligosaccharides [ 19 ], which may be important in improving immunity in infants. Interestingly, studies involving children aged from 3 to 16 showed that the levels of both hBD-1 and hBD-2 in saliva increased with age, which concurs with the maturation of the immune system [ 20 ].…”
Section: Hbd-2 and Oral Cavity Epitheliummentioning
confidence: 99%
“…This study is focused on mono- and disaccharides. The role of dietary oligosaccharides and polysaccharides in regulating HDP gene expression is largely unknown, except that two human milk oligosaccharides were recently found to increase human β-defensin 2 protein synthesis, but not other HDPs or inflammatory cytokines ( Gursoy et al, 2021 ). It will be interesting to explore possible HDP-inducing and other immunomodulatory roles of commonly used dietary oligosaccharides and polysaccharides such as fructo-oligosaccharides, galacto-oligosaccharides, xylo-oligosaccharides, mannan-oligosaccharides, and inulin, all of which are being actively explored as prebiotics to manage the gut microbiome, gut health, and diseases ( Zhu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cellular responses of the organotypic oral mucosal model were stimulated as described previously. 22 The model was activated with P. gingivalis (3×10 6 CFU), F. nucleatum (3×10 6 CFU), P. gingivalis LPS (10 ng), and IL‐1β (150 pg) using a nitrocellulose filter as a scaffold. An organotypic model with only the membrane filter formed the control group.…”
Section: Methodsmentioning
confidence: 99%